2012
DOI: 10.1103/physreva.86.064701
|View full text |Cite
|
Sign up to set email alerts
|

Long-range interactions between excited helium and alkali-metal atoms

Abstract: The dispersion coefficients for the long-range interaction of the first four excited states of He, i.e., He(2 1,3 S) and He(2 1,3 P), with the low-lying states of the alkali-metal atoms Li, Na, K, and Rb are calculated by summing over the reduced matrix elements of the multipole transition operators. For the interaction between He and Li the uncertainty of the calculations is 0.1-0.5%. For interactions with other alkali-metal atoms the uncertainty is 1-3% in the coefficient C 5 , 1-5% in the coefficient C 6 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…The Lennard-Jones potential is given by V b (r) = −(C 6 /r 6 ) 1 − b/r 6 , where we can tune the depth of the potential, and therefore a, by parameter b. Note that the less accurate C 6 coefficient of Zhang et al [15] gives the same result than the one obtained in this work, showing that a few percent accuracy is sufficient.…”
Section: Estimate Of Accuracy Ccsd(t) Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…The Lennard-Jones potential is given by V b (r) = −(C 6 /r 6 ) 1 − b/r 6 , where we can tune the depth of the potential, and therefore a, by parameter b. Note that the less accurate C 6 coefficient of Zhang et al [15] gives the same result than the one obtained in this work, showing that a few percent accuracy is sufficient.…”
Section: Estimate Of Accuracy Ccsd(t) Methodssupporting
confidence: 65%
“…We therefore have calculated the dipolar-and quadrupole dynamic polarizabilities of He * at imaginary frequencies and integrated , which has an accuracy of 0.56%. Finally we include the C 10 coefficient from Zhang et al [15] to the long-range part of our potential.…”
Section: Ab Initio Calculationsmentioning
confidence: 99%
“…For the C 8 and C 10 coefficients we have used the values calculated by Zhang et al [43] for which the authors estimated an uncertainty of about 1%-10%. However, our study of the He * +Rb system has shown that the error bounds for the C 8 coefficient given by Zhang et al were also far too conservative [18].…”
Section: Long-range Potentialmentioning
confidence: 99%
“…For He, the energy spectra and reduced matrix elements of the multipole transition operators are the same as those used for calculating the dispersion coefficients for the low-lying states [19][20][21][22][23][24] and the polarizabilities of Rydberg states [25]. The wave functions are expanded in terms of Hylleraas-type basis functions,…”
Section: P 16mentioning
confidence: 99%